2023
DOI: 10.1038/s42003-022-04394-6
|View full text |Cite
|
Sign up to set email alerts
|

Plagued by a cryptic clock: insight and issues from the global phylogeny of Yersinia pestis

Abstract: Plague has an enigmatic history as a zoonotic pathogen. This infectious disease will unexpectedly appear in human populations and disappear just as suddenly. As a result, a long-standing line of inquiry has been to estimate when and where plague appeared in the past. However, there have been significant disparities between phylogenetic studies of the causative bacterium, Yersinia pestis, regarding the timing and geographic origins of its reemergence. Here, we curate and contextualize an updated phylogeny of Y.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…So far, retrieving temporal information on the Y. pestis phylogeny has been done primarily by applying molecular dating, although the applicability has been questioned because of a lack of a temporal signal in some studies 4,23,24 . In a recent study, demonstrated that the temporal signal across the entire species is unstable but increases significantly when considering only subclades 25 . However, the study was also able to show that Y. pestis has a high phylodynamic threshold (estimated to one substitution per 1.1 to 14.1 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, retrieving temporal information on the Y. pestis phylogeny has been done primarily by applying molecular dating, although the applicability has been questioned because of a lack of a temporal signal in some studies 4,23,24 . In a recent study, demonstrated that the temporal signal across the entire species is unstable but increases significantly when considering only subclades 25 . However, the study was also able to show that Y. pestis has a high phylodynamic threshold (estimated to one substitution per 1.1 to 14.1 years).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the mean date is used as a tip date for molecular dating 2,4,25 instead of uniform distributions of the 2-σ intervals 28 or the full probability distribution 29 . This results in an 'artificial' precision, causing too narrow (and erroneous) intervals for dates of most recent common ancestors (MRCA) 25 , which could be one explanation for discrepancies between molecular dating analyses and historical analyses regarding the emergence of pandemics 25 .…”
Section: Discussionmentioning
confidence: 99%
“…We chose this method in favour of the ‘tip calibration’ approach used by prior studies, which infer node ages and a substitution rate by incorporating heterochronous sequences into their phylogeny 72 , 73 . In addition to requiring adequate temporal structure 74 , 75 , tip dating is liable to the time dependent rate phenomenon 76 , 77 (TDRP), which systematically underestimates the ages of deep nodes of a tree (see Discussion). Node calibration, while not subject to the TDRP, does, however, rely on a robust biogeographic or genetic model to justify the codivergence scenario proposed 72 , 73 , 78 (see Discussion).…”
Section: Resultsmentioning
confidence: 99%
“…As the phage is only present in one modern phylogenetic sub-branch, it is possible to estimate the approximate time of its incorporation based on the molecular dating of the splits in the phylogeny. Molecular dating depends on various factors, such as the included strains and the methods used for the analysis, and thus there seems to be no consensus in the literature concerning the exact date of the 1.ORI branch split [ 35 ]. Although the 1.ORI branch could have emerged anytime between approximately 550 and 150 years ago [ 9 , 35 37 ], it is likely that both the split and the genomic acquisition of Ypf Φ occurred before the Modern plague pandemic.…”
Section: Discussionmentioning
confidence: 99%